Analisis Faktor Eksploratori dan Konfirmatori untuk Validasi Skala Lingkungan Makan Terstruktur pada Ibu Bekerja - Rohmah Rifani; Suryanto Suryanto; Dewi Retno Suminar (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to develop and validate the construct of structured meals environment scale. The method used was a cross-sectional survey. The participants were working mothers with early-aged children. The structured meals environment scale used Likert scale which consists of three dimensions: structured meals setting, structured meals timing, and family meals setting. The results of EFA (N = 302) showed that the scale explains the construct of a structured meals environment was 63.98%. The results of CFA (N = 202) showed that the goodness of fit model was acceptable. Factors loading > .5 (.503 - .819) shows the items are valid. Discriminant validity (AVE) moves from .482 - .577 with construct reliability > .7 (.760 - .802). Structured meals environment scale has met the psychometric property test so that the scale is proper to be used.